ALLN rescues an in vitro excitatory synaptic transmission deficit in Lis1 mutant mice - Sebe, Joy Y. (American Physiological Society, 2013)
LIS1 gene mutations lead to a rare neurological disorder, classical lissencephaly, characterized by brain malformations, mental retardation, seizures, and premature death. Mice heterozygous for Lis1 (Lis1(+/−)) exhibit cortical malformations, defects in neuronal migration, increased glutamate-mediated synaptic transmission, and spontaneous electrographic seizures. Recent work demonstrated that in utero treatment of Lis1(+/−) mutant dams with ALLN, a calpain inhibitor, partially rescues neuronal migration defects in the offspring. Given the challenges of in utero drug administration, we examined the therapeutic potential of ALLN on postnatal lissencephalic cells. Voltage- and current-clamp studies were performed with acute hippocampal slices obtained from Lis1 mutant mice and age-matched littermate control mice. Specifically, we determined whether postnatal ALLN treatment can reverse excitatory synaptic transmission deficits, namely, an increase in spontaneous and miniature excitatory postsynaptic current (EPSC) frequency, on CA1 pyramidal neurons observed in tissue slices from Lis1(+/−) mice. We found that acute application of ALLN restored spontaneous and miniature EPSC frequencies to wild-type levels without affecting inhibitory postsynaptic synaptic current. Furthermore, Western blot analysis of protein expression, including proteins involved in excitatory synaptic transmission, demonstrated that ALLN blocks the cleavage of the calpain substrate αII-spectrin but does not rescue Lis1 protein levels in Lis1(+/−) mutants.